ANALISIS CUSTOMER VALUE DALAM MEMEDIASI PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP REPUTASI UNIVERSITAS SWASTA DI KOTA BATAM - Nur Elfi Husda (Institute of Research and Community Outreach - Petra Christian University, 2019)
The purpose of this study is to determine the effect of Management Information Systems and customer value to the achievements of private universities in the city of Batam. The study population is a private university student enrolled in Management programs that has B accreditation in Batam city. Data analysis techniques used in explaining the phenomenon in this study is Structural Equation Modeling (SEM). The results of the study show that better Management Information System will increase students' assessment of the University, as well as the student's assessment of the university's reputation, but the good or bad of the Management Information System does not affect the reputation of the university. A better Management Information System, will further enhance the reputation of the university if the student's assessment of the university is also good.